2018
DOI: 10.3390/bioengineering5040096
|View full text |Cite
|
Sign up to set email alerts
|

Polo-Like Kinase 4 (PLK4) Is Overexpressed in Central Nervous System Neuroblastoma (CNS-NB)

Abstract: Neuroblastoma (NB) is the most common extracranial solid tumor in pediatrics, with rare occurrences of primary and metastatic tumors in the central nervous system (CNS). We previously reported the overexpression of the polo-like kinase 4 (PLK4) in embryonal brain tumors. PLK4 has also been found to be overexpressed in a variety of peripheral adult tumors and recently in peripheral NB. Here, we investigated PLK4 expression in NBs of the CNS (CNS-NB) and validated our findings by performing a multi-platform tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Polo‐like kinases are important regulators in cell cycle and DNA damage response, which are shown to be closely related to pathogenesis of cancers. In vitro study reports that PLK4 promotes tumor cell proliferation, survival, invasion, and migration in central nervous system neuroblastoma and increases tumor growth . And in pancreatic cancer, the inhibitor of PLK4 results in a significant reduction of tumor initiating cells .…”
Section: Discussionmentioning
confidence: 99%
“…Polo‐like kinases are important regulators in cell cycle and DNA damage response, which are shown to be closely related to pathogenesis of cancers. In vitro study reports that PLK4 promotes tumor cell proliferation, survival, invasion, and migration in central nervous system neuroblastoma and increases tumor growth . And in pancreatic cancer, the inhibitor of PLK4 results in a significant reduction of tumor initiating cells .…”
Section: Discussionmentioning
confidence: 99%
“…PLK4 has also been recognized as a promising therapeutic target for numerous tumors 29 . Moreover, previous studies determined that PLK4 level was upregulated in NB, and the deficiency of PLK4 weakened NB aggressive progression 30,31 . Here, we first identified that PLK4 is a functionally important target of miR‐513c‐5p in regulating malignant NB cell progression in vitro.…”
Section: Discussionmentioning
confidence: 77%
“…29 Moreover, previous studies determined that PLK4 level was upregulated in NB, and the deficiency of PLK4 weakened NB aggressive progression. 30,31 Here, we first identified that PLK4 is a functionally important target of miR-513c-5p in regulating malignant NB cell progression in vitro. Furthermore, we showed that DLX6-AS1 functioned as a posttranscriptional regulator of PLK4 expression by sponging miR-513c-5p.…”
Section: Discussionmentioning
confidence: 99%
“…All told, the targeting of PLK4 appears to be a promising new anticancer strategy. As to childhood cancers, PLK4 has been reported to be overexpressed in patient-derived rhabdoid tumour and neuroblastoma samples (Sredni et al 2017b ; Tian et al 2018 ; Bailey et al 2018 ). Moreover, PLK4i have been shown to exert anticancer activities against cultured rhabdoid tumour, medulloblastoma and neuroblastoma cells (Sredni et al 2017a , b ; Suri et al 2019 ; Tian et al 2018 ), but they have not yet been tested in ES cells.…”
Section: Introductionmentioning
confidence: 99%